Pengaruh Literasi Keuangan Terhadap Keputusan Penggunaan Produk Pegadaian Syariah - Mallfi Lutfia; Herlina Yustati (SANTRI : Jurnal Ekonomi dan Keuangan Islam, 2024)
This research aims to analyze the influence of financial literacy on decisions to use sharia pawnshop products. Financial literacy is an important factor that influences individuals in making financial decisions, including choosing sharia-based financial products. In this context, sharia pawnshops are one of the financial institutions that offer financing solutions according to sharia principles. This study uses a quantitative method with a survey approach to sharia pawnshop customers. Data were analyzed using linear regression to measure the relationship between the level of financial literacy and the decision to use sharia pawnshop products. The research results show that financial literacy has a significant influence on customers' decisions in using sharia pawnshop products. The higher the customer's financial literacy, the more likely they are to choose sharia pawnshop products as a financing solution. These findings underline the importance of financial education in increasing community participation in using sharia financial services. The results of the study indicate that simultaneously the variables of financial knowledge, financial management skills, and attitudes towards Islamic finance together have a significant influence on the decision to use Islamic Pawnshop products. The results of multiple linear regression analysis indicate that financial knowledge, skills and financial management have a significant effect on the decision to use Islamic Pawnshop products. Increasing financial knowledge, skills and financial management will increase the decision to use Islamic Pawnshop products.